Potensi Eco-Cycling Ekowisata Subak Sembung, Di Desa Peguyangan, Kecamatan Denpasar Utara - Kristin, Debora; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
Purpose Of Research Singer is for the review to know the potential of eco-cycling in ecotourism Subak Sembung.This research was conducted using qualitative method. Data were collected through observation and in-depth interviews, documentation and study of literature. Informant determining technique using purposive sampling, by selecting the source is considered to have a deep knowledge of the potential that exists in Subak Sembung. Chairman of the manager and the people who know the history of Subak Sembung.Data were analyzed using the concept of ecotourism by Fennel (Arida, 2009) and the World Conservation Union (WCU in Arida, 2009) and is supported by the concept of potential and cycling that gets results that Subak Sembung has very good potential to conduct eco-cycling.The local community has a major role in the management of eco-cycling activities. When people are getting ready to activities that will promote the activities of the new travel package that is eco-cycling in the middle of Denpasar.   Keywords : ecotourism, potential, eco-cycling